Effect of warm compress and breathing technique on duration of the second stage of labor - Anisa, Fadhiyah Noor; Palimbo, Adriana; Maolinda, Winda; Yuliyana (Ananda - Health & Education Foundation, 2023)
Background: The duration of the second stage of labor is a stage of risk for the well-being of the fetus. The average time limit for the second stage in primiparas is less than two hours; in multigravidas, it is less than one hour. Several techniques developed non-pharmacologically are intended to shorten the duration of labor and minimise complications in the mother and fetus. Objective: To analyse the effect of the warm compress technique with a combination of warm compress and breathing techniques on the duration of the second stage of labor. Methods: This type of research is done through two measurements, including experiments and observations. The number of samples is 20 women in stage II. Samples were divided into two groups. The control group consisted of 10 people using warm compresses, while the experimental group of 10 people was given warm compresses and breathing techniques. Labor pain instruments use the Numeric Rating Scale (NRS). Results: The results of paired differents showed that there was an effect of giving warm compresses combined with breathing technique in adapting labor pain (p-value 0.000<0.05) compared to only warm compresses (p-value 0.0965). Moreover, for the findings of equal means, the experimental group's pain scale was lower than the control group (p-value 0.000<0.05). Meanwhile, the results of the Pearson correlation obtained the value of Sig. (0.041), the variable stage I pain scale and stage II duration correlate significantly. Conclusion: Non-pharmacological techniques with warm compresses and breathing techniques affect a low pain scale. And also a significant correlation between the two variables, namely the pain of the first stage and the duration of the second stage.